A new scoring system for risk stratification of thyroid tumors - Ya Yuan; Hua Shu; Lu Li; Liuxi Wu; Fei Yu (BMC Medical Imaging)
Abstract Objectives To develop an ultrasound feature–based risk stratification system for differentiating benign, low-risk and malignant thyroid tumors and compare it with existing TI-RADS. Methods The retrospective study included patients who underwent preoperative neck ultrasound examination from January 2018 to June 2023, and their ultrasound characteristics were recorded. According to surgical pathological findings, they were classified into three categories: benign, low-risk, and malignant. Univariable and multivariable logistic regression analyses were used to assess the association of qualitative ultrasound features with different risk stratifications and a new scoring system was established to evaluate its diagnostic efficacy, and to compare it with TI-RADS. Results Aspect ratio ≥1 was an independent risk factor in the comparison of benign and low-risk thyroid nodules, and in the comparison of benign and malignant nodules, hypoechoic,irregular margin,nodule max diameter ≤1 cm,the aspect ratio ≥1 and elasticity score ≥3 were independent risk factors. According to the multivariate analysis, they were assigned 1, 2, 2, 3, 2/4 points respectively, and we established a new scoring system. According to ROC analysis, the total score of 0–4.5 was considered as benign nodules, 4.5–5.5 was considered as low-risk nodules, and more than 5.5 were considered as malignant nodules. Compared it to ACR-TI-RADS, this scoring system performed better than in differentiating benign and malignant nodules (P = 0.001, P = 0.018, respectively). Conclusion The scoring system based on ultrasound features established in this study can be used for risk stratification of thyroid nodules more efficiently, it has higher sensitivity and specificity for the differentiation of benign and malignant nodules.